Anabolic–androgenic steroids: How do they work and what are the risks? - Bond, Peter; Smit, Diederik L.; de Ronde, Willem (Frontiers in Endocrinology, 2022)
Anabolic–androgenic steroids (AAS) are a class of hormones that are widely abused for their muscle-building and strength-increasing properties in high, nontherapeutic, dosages. This review provides an up-to-date and comprehensive overview on how these hormones work and what side effects they might elicit. We discuss how AAS are absorbed into the circulation after intramuscular injection or oral ingestion and how they are subsequently transported to the tissues, where they will move into the extravascular compartment and diffuse into their target cells. Inside these cells, AAS can biotransform into different metabolites or bind to their cognate receptor: the androgen receptor. AAS and their metabolites can cause side effects such as acne vulgaris, hypertension, hepatotoxicity, dyslipidemia, testosterone deficiency, erectile dysfunction, gynecomastia, and cardiomyopathy. Where applicable, we mention treatment options and self-medication practices of AAS users to counteract these side effects. Clinicians may use this review as a guide for understanding how AAS use can impact health and to assist in patient education and, in some cases, the management of side effects.